Pepsin digestibility of proteins in sorghum and other major cereals - Mertz, Edwin T. (1984)
We have shown previously that sorghum is highly digestible in the rat. However, other workers have shown that sorghum is much less digestible than wheat, maize, and rice in young children. Because the rat does not show these digestibility differences, we developed an empirical pepsin digestion method, first reported in 1981, which simulates the digestion values found in children. In this report the method has been improved and used to analyze wheat, maize, rice, millet, and sorghum and certain processed samples of millet and sorghum. The pepsin digestion values parallel those found in children for wheat, maize, rice, and sorghum. In addition, a processed sorghum product that gave a high digestion value in children also gave a high value with the in vitro pepsin method.